2023
DOI: 10.1177/08997640231172209
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: Social Information on Reference Groups and its Influence on Volunteering Intention—A Survey Experiment

Magdalena Henninger,
Maren Rottler,
Bernd Helmig

Abstract: Voluntary contributions are a crucial resource for nonprofit organizations and challenging to acquire. Social information on other people’s contributions has been found to positively influence individual giving behavior. However, a clear understanding how social information reference groups impact volunteering intentions is missing. Drawing on social comparison theory, we conducted a survey experiment with variations in social information reference groups to shed light on mechanisms within social comparison pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Families working in agriculture may contribute to the development of attitudes in adolescents conducive to volunteering through the socialization process and role modelling [37]. The researchers found that identification with a group is a key factor in explaining volunteering intentions [55]. The family is a significant reference group which shows its role in explaining adolescent volunteering.…”
Section: Resultsmentioning
confidence: 98%
“…Families working in agriculture may contribute to the development of attitudes in adolescents conducive to volunteering through the socialization process and role modelling [37]. The researchers found that identification with a group is a key factor in explaining volunteering intentions [55]. The family is a significant reference group which shows its role in explaining adolescent volunteering.…”
Section: Resultsmentioning
confidence: 98%